التأثير التثبيطي للمستخلص الزيتي لنبات الحبة السوداء والسماق والفلفل الأسود على نمو جراثيم الزوائف المسببة لفساد سمك الترويت - عراونة عبد العزيز; القوجة خلدون (Latakia University Journal -Biological Sciences Series, 2018)
The research aims to study the possibility of prolonging the period of keeping fish meat (trout) Using treated extracts of the oily plant of Nigella Sativa, Rhas Coriaria and Piper Nigrum, as well as to curb the role of germs pseudomonas in fish flesh spoilage through conservation radiator with over the counter effect of oil . The samples of fish meat which studied have dived in the oil extracts for one minute and then preserved at a temperature of 4 ± 1 ° C for 15 days. It has been studing the effect of different oily extracts during the extended conservation 0, 3, 7, 10 and 15 days in a bacterial load, including the total enumeration of spores in a way (ISO 4833) and total enumeration of pseudomonas. It was also identified the value of pH and some sensory and physical qualities of meat such as color, smell and texture and taste. The results showed that the oily extracts have effectively influenced the lengthening keep trout, while remaining fresh and sensual qualities of having good for more than 10 days compared to the control, which did not exceed a period of 7 to save the day. Treatment sample showed oil extracted by Nigella Sativa recipes better quality during periods of conservation and the best inhibitor to the growth of the bacteria pseudomonas in the cooling temperature 4 ± 1 ° C . يهدف البحث إلى دراسة إمكانية إطالة مدة حفظ لحوم الأسماك (الترويت) عن طريق معاملته بالمستخلصات الزيتية لنبات الحبة السوداء والسماق والفلفل الأسود وكذلك كبح دور جراثيم الزوائف في فساد لحم السمك خلال الحفظ المبرد من خلال الأثر المضاد للمستخلصات الزيتية عليها. حيث غطست عينات لحوم الأسماك المدروسة بالمستخلصات الزيتية لمدة دقيقة واحدة ثم حفظت عند درجة 4±1 م° مدة 15 يوم. دُرِسَ تأثير المستخلصات الزيتية المختلفة خلال مدد الحفظ 0 و 3 و 7 و 10 و 15 يوم على الحمولة الجرثومية بما فيها التعداد الكلي للجراثيم بطريقة ((ISO 4833 والتعداد الكلي لجراثيم الزوائف. كما تم تحديد قيمة الـ pH وبعض الصفات الحسية والفيزيائية للحم كاللون والرائحة والقوام والطعم. وقد بينت النتائج أن المستخلصات الزيتية قد أثرت تأثيراً فعالاً في إطالة مدة حفظ سمك الترويت مع بقائه طازجاً وامتلاكه صفات حسية جيدة مدة تزيد على 10 يوم مقارنة بالشاهد الذي لم تتجاوز مدة حفظه 7 يوم . وقد أظهرت العينة المعاملة بالمستخلص الزيتي للحبة السوداء أفضل صفات جودة خلال مدد الحفظ وأفضل مثبط لنمو جراثيم الزوائف في درجة حرارة التبريد4±1 م°.